Breast Cancer: When the Woman You Love Has Breast Cancer - Martha C. Monroe; Barbara F. Shea; Linda B. Bobroff (EDIS, 2007)
FCS8826, a 3-page fact sheet by Martha Monroe, Barbara Shea, and Linda Bobroff, is designed to help partners of people who have been diagnosed with breast cancer. This publication will assist partners in supporting the patient and finding the best ways to help her and also provides tips to help partners cope with the stresses of this period. Published by the UF Department of Family, Youth and Community Sciences, February 2007.